Religiosity and Life Satisfaction in Indonesia: Evidence from a Community Survey - Vera Nur Choirina; Yulia Ayriza; Yoga Setyo Wibowo (Universitas Ahmad Dahlan, 2021)
There is a growing interest in the relationship between religiosity and subjective well-being in the literature. However, little evidence exists from Indonesia with a national scope. The aim of this study was to contribute to the literature by investigating the association between self-perceptions of religiosity and life satisfaction using nationally representative data from the Indonesia Family and Life Survey. Linear regression was used for data analysis with a sample of 27,150 individuals aged between 18 and 90. The main findings showed that those who were religious were more satisfied with their life than their counterparts, even after controlling for a set of confounding variables. It seems that religiosity provides people with well-being benefits which might lead to the good life.